Long-Term Effects of Sports Concussions: Bridging the Neurocognitive Repercussions of the Injury with the Newest Neuroimaging Data. (October 2017) - Henry, Luke C.; Tremblay, Sebastien; De Beaumont, Louis
Little is known of the long-term effects of sports-related concussion. Within the scientific literature, conclusions vary substantially where some work suggests there are no long-term consequences at all and other studies show rampant neurodegeneration thought to be caused by sometimes even a single concussive blow to the head. There is growing evidence that supports multiple long-term outcomes, showing both subclinical and clinically relevant changes in the brains of athletes, young and old alike. This article reviews the pathohistology of cerebral concussions and examines the extant literature with a focus on electrophysiological and neuroimaging findings. Neurobehavioral and neurocognitive changes are also reviewed, particularly as they are related to chronic traumatic encephalopathy. Lacunae within the literature are explored, and future research directions are proposed.